Financial Constraint dan Sensitivitas Pembiayaan Eksternal Terhadap Aliran Kas - Excel, Alexander; Kuang, Tan Ming (Universitas Muhammadiyah Metro, 2024)
Based on the pecking order theory, companies prefer internal funding sources over external (debt and equity) due to information asymmetry problems (d.k.l., financial constraints). However, this theory does not anticipate that external financing components may respond differently to cash flows. This research replicates a study conducted by Park (2019) to examine the influence of cash flow on external funding components and the sensitivity of external funding to cash flow which is moderated by financial constraints in the Indonesian context. This research is a quantitative study that observed 978 financial data of public companies in Indonesia during 2016-2019 and analyzed using ordinary least squares. This research finds that cash flow is negatively related to external funding, except for long-term debt and equity, the substitution between internal funding and debt is carried out using short-term debt, and the sensitivity of external funding to cash flow is stronger for companies with funding without constraints. This research concludes that the agency problem is not the sole factor in determining funding decisions for future study companies to expand the observation year and use other financial constraint criteria such as bonds and commercial paper ratings.